Annual Plan 1995-96 (Sectoral Plans) Vol II Government of Nagaland - Planning Commission (Planning Commission, 1995)
The State Planning Machinery was set up in 1 973 with a small nucleus of Officers ‘and Staff under the Administrative control of Home Department, Initially, the expenditure of Staff salaries and Office expenses were borne between the Centre and the State on a 2/3 end 1/3 basis respectively. This a arrangement has now been discontinued from 1986-87 and the expenses of the Department is now direct scheme under State resources
Planning and Coordination Department Nagaland, Kohima
Planning Commission
Keywords: Planning Machinery; Tourism; Survey & Statistics; Food & Civil Supplies; Weights & Measures; Evaluation; School Education; Higher & Technical Education; Youth Resources & Sports; Arts & Culture; Health & Family Welfare